Edukasi Pencegahan Kanker Payudara dan Pengenalan Potensi Tanaman Kelakai (Stenochlaena palustris) untuk Mencegah Kanker Payudara - Harlyanti Muthma'innah Mashar; Dali Dali (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The incidence of breast cancer does not only occur in the age range of 30–50 years but has also been found in adolescence. It is necessary to conduct early prevention education of breast cancer and its potential as a local plant in preventing breast cancer. It is hoped that the implementation of this activity can support cancer control activities by utilizing local wisdom typical of Central Kalimantan. The target of this activity is students at MAN Palangka Raya City. Implementation methods in the form of posttest and pretest, interactive counseling through zoom applications, and discussion. The implementation of the posttest and pretest aims to see an increase in understanding after counseling. The value obtained from the posttest and pretest results was then performed statistical tests using the paired T-test. Based on the results of the analysis, it was found that there was a significant difference in knowledge between before and after counseling, as evidenced by an increase in posttest scores. The average posttest score was 85.34. This value is greater than the pretest average value of 80.01. Based on the results of the paired T-test, it is known that the p-value (asymp. sig 2 tailed) is 0.001 (p <0.05), thus it is concluded that there is a significant difference in knowledge between before extension and after counseling. As many as 80% of participants have a good level of knowledge. This has achieved an indicator of success, where more than 75% of extension participants can understand the material provided.